Cost-effectiveness of fondaparinux versus enoxaparin in non-ST-elevation acute coronary syndrome in Canada (OASIS-5). Issue 1 (December 2015) - Alfonso Ross Terres, Jorge; Lozano-Ortega, G.; Kendall, R.; Sculpher, M.
Abstract Background Acute coronary syndrome (ACS) refers to a spectrum of life-threatening cardiac diseases usually due to coronary artery plaque rupture, subsequent thrombin generation plaque activation and thrombus formation. To date, no economic analyses have been published about the use of fondaparinux in NSTE-ACS patients in Canada. The purpose of our study is to estimate the lifetime cost-effectiveness of fondaparinux compared to enoxaparin for non-ST-elevation acute coronary syndrome (NSTE-ACS) patients in a Canadian hospital setting. Methods As an extension of a previous published economic analysis for US patients, an event-based decision analytic model was constructed using clinical and resource use data from OASIS-5, a randomized trial of 20, 078 patients from 41 countries. A public payer perspective in the hospital setting was adopted. Resource use data from the trial were valued using Canadian costs. A cost regression model was developed to estimate the mean cost of managing the clinical events over the 180 day period. Annual costs of long-term care for ACS patients were added after 180 days until death. Long-term survival was incorporated using Canadian life tables with further adjustment for additional risks associated with NSTE-ACS. Quality-of-life (utility) decrements from published sources were applied to clinical events. Lifetime costs (2009 CAD$) and quality-adjusted life-years (QALYs), discounted annually at 5 %, were estimated for the typical patient in OASIS-5 (i.e., at mean covariate values). Results The trial data showed that fondaparinux is protective against all clinical events observed in the trial. The model showed that: over 180 days, fondaparinux dominates enoxaparin, producing similar estimates of QALYs gained and saving $439; over a patient's lifetime, fondaparinux yields an ICER of $4293/QALY. Based on PSA, the probabilities that fondaparinux dominates enoxaparin (less costly and more effective) and that is cost-effective at a $50, 000 threshold were 42 % and 96 %, respectively. Conclusions In the Canadian hospital setting, fondaparinux is cost-effective when compared to enoxaparin for the treatment of NSTE-ACS. This result holds both in the immediate post-event period and over the lifetimes of patients.